2015
DOI: 10.1155/2015/673018
|View full text |Cite
|
Sign up to set email alerts
|

Is Lipoprotein-Associated Phospholipase A2 a Link between Inflammation and Subclinical Atherosclerosis in Rheumatoid Arthritis?

Abstract: Objective. Lipoprotein-associated phospholipase A2 (Lp-PLA2), a marker of vascular inflammation, is associated with cardiovascular disease. This prospective study of an inception cohort aimed to investigate whether the level of Lp-PLA2 is associated with subclinical atherosclerosis in patients with rheumatoid arthritis (RA). Methods. Patients from northern Sweden diagnosed with early RA were consecutively recruited into an ongoing prospective study. From these, all patients ≤60 years (n = 71) were included for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Atherosclerosis is nowadays recognized as an inflammatory disease and there are many parallels between the pathological and immunological processes that occur in the synovium and the atheromatous lesions in the vessel walls [6]. A previous published study on the same individuals as in this study has suggested lipoprotein-associated phospholipase A2 (Lp-PLA2) as one of the biomarkers that might be able to indicate that, over time, the deleterious disease process in RA may also affect the vascular walls [16].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is nowadays recognized as an inflammatory disease and there are many parallels between the pathological and immunological processes that occur in the synovium and the atheromatous lesions in the vessel walls [6]. A previous published study on the same individuals as in this study has suggested lipoprotein-associated phospholipase A2 (Lp-PLA2) as one of the biomarkers that might be able to indicate that, over time, the deleterious disease process in RA may also affect the vascular walls [16].…”
Section: Discussionmentioning
confidence: 99%
“…In organisms, there are more than 14 different species of PLA 2 enzymes, which may play different or similar roles in many biological processes. Among these 14 isoforms, four main subtypes of PLA 2 include the cytosolic phospholipase A 2 (cPLA 2 ), calcium-independent phospholipase A 2 (iPLA 2 ), secreted phospholipase A 2 (sPLA 2 ), and the platelet activating factor acetyl hydrolase/oxidized lipid lipoprotein-associated phospholipase A 2 (LpPLA 2 ) are widely studied and identified by researchers ( Kozaki et al, 2015 ; Sodergren et al, 2015 ). cPLA 2 is one of the main subtypes produced in the inflammation area and also the only one PLA 2 with a catalyzed-hydrolysis peculiarity for arachidonic acid (AA) at the position of sn-2 in phospholipids ( Hartz et al, 2019 ).…”
Section: Therapeutic Enzymes and Their Derivatives In Ramentioning
confidence: 99%
“…In a cohort of rheumatoid arthritis (RA) patients, the baseline Lp‐PLA2 mass was significantly associated with both disease severity and subclinical atherosclerosis including IMT and flow‐mediated dilation at both baseline and follow‐up. Consequently, Lp‐PLA2 might be a biomarker of vascular damage among patients with RA . In addition, a prospective longitudinal cohort study identified the plasma Lp‐PLA2 activity and mass, which were independently and significantly associated with incident abdominal aortic aneurysm (AAA), as markers of AAA risk …”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 99%
“…Consequently, Lp-PLA2 might be a biomarker of vascular damage among patients with RA. 232 In addition, a prospective longitudinal cohort study identified the plasma Lp-PLA2 activity and mass, which were independently and significantly associated with incident abdominal aortic aneurysm (AAA), as markers of AAA risk. 17 Certain relationships between Lp-PLA2 and these diseases were already detected; however, further research is needed for a deeper understanding of the associations.…”
mentioning
confidence: 99%